Scalable, Ultrathin, and High‐Temperature‐Resistant Solid Polymer Electrolytes for Energy‐Dense Lithium Metal Batteries. Issue 15 (25th February 2022) - Ma, Yinxing; Wan, Jiayu; Yang, Yufei; Ye, Yusheng; Xiao, Xin; Boyle, David T.; Burke, Will; Huang, Zhuojun; Chen, Hao; Cui, Yi; Yu, Zhiao; Oyakhire, Solomon T.; et al.
Abstract: All‐solid‐state batteries (ASSBs) demonstrate great promise, offering high energy density, good thermal stability, and safe operation compared with traditional Li‐ion batteries. Among various solid‐state electrolytes (SSEs), solid polymer electrolytes (SPEs) offer an attractive choice due to their thinness, low density, and good manufacturability. However, ultrathin SPEs that work with practical current densities or at high temperatures remain challenging, limiting applicable conditions of SPE‐based batteries. Here, the authors report a novel scalable, ultrathin, and high‐temperature‐resistant SPE for ASSBs. This design includes an electrospun polyacrylonitrile (PAN) matrix and polyethylene oxide (PEO)/Li salt ionic conductor, which offers a stable LiF and Li3 N containing SSE/Li interface. The unique interface—as well as the good mechanical strength—inhibits lithium dendrites and prevents short circuiting. As a result, symmetrical LiLi cells deliver more than 300 h cyclability at 0.5 mA cm −2 . ASSBs fabricated with only 5 µm‐thickness PAN‐PEO/lithium bis(trifluoromethanesulfonyl)imide reach 300 cycles at 0.3 C rate at 60 °C. The excellent thermal stability of PAN also results in safer SPEs at high temperatures. The design extends battery operation up to temperatures of 120 and 150 °C, where it achieves 500 cycles at C/2 rate and 100 cycles at 2C rate, respectively. Abstract : Polyacrylonitrile‐based solid polymer electrolytes (SPEs) with high mechanical strength, good interfacial stability with Li metal, and excellent thermal stability are prepared through electrospinning and calendaring, followed by infiltration of polyethylene oxide/lithium bis(trifluoromethanesulfonyl)imide. This design overcomes the inherent limitations of traditional SPEs, realizing safe operation of 5 μm‐ultrathin SPEs, and achieving excellent cycling stability for all‐solid‐state batteries at an extreme temperature of 150 °C.